Defiance and Opportunity of Marketing Performance of Rural Bank in Indonesia - Suryadi, Nanang; Hakim, Abdurrahman; Fasieh, Muhammad Fajrul Islam; Gulam B, Muhammad Irsyad; Hidayat, Bambang Samsul (Universitas Syiah Kuala, 2023)
Objective A massive advance in the digital era has changed customer habits, and marketing has even changed these past few years. Banking service started focusing on customer relation. The government policy also contributed a lot in law paying for the implementation of banking technology. This research was aimed at identifying the effects of technology, government, and customers on marketing performance through the mediation of human resources. This research was conducted at Rural Banks in Indonesia.Design/Methodology This research utilized Partial Least Square- Structural Equation Model (PLS-SEM). The samples of research were 184 respondents who have already known the marketing condition in Rural Banks.Results The research result referred that a number of factors relating to technology, government, and customer have significant effects on marketing performance. The human resource played a role in mediating the effects of technology and government on marketing performance partially.Contribution This research showed that the effect of technology, government, and customer were able to trigger a good improvement of marketing performance. Further, the practical contribution indicated that the marketing performance was needed and required by Rural Bank in this digital era.Novelty/Originality This paper contributes to the rural bank literature by providing a unique overview of the field of corporate performance research. The study also utilizes a unique methodology by sampling a variety of different objects. By adopting a comprehensive strategy, this study aims to provide a more holistic perspective on marketing performance, especially in the field of rural banking